염기성 밭 토양에서 안정화제에 의한 엽채류, 근채류, 과채류 작물들의 중금속 전이 특성 - 김민석(Min-Suk Kim); 민현기(Hyun-Gi Min); 이상환(Sang-Hwan Lee); 김정규(Jeong-Gyu Kim) (Ecology and Resilient Infrastructure, 2020)
Various types of amendments have been studied for heavy metal stabilization in soil. However, researches on the effect of amendments on alkali soil and their effects on the plants at various edible parts are insufficient. The aim of this study was to evaluate the stabilization efficiency of heavy metals and their transfer into edible parts of food crops. Abandoned mine area was selected and 3 types of amendments (lime stone, LS; steel slag, SS; acid mine drainage sludge, AMDS) was applied with 3% (w/w). in field. After 6 month aging, Chinese cabbage (leafy), bok choy (leafy), garlic (root) and red pepper (fruit) were transplanted and cultivated. For chemical assessment, total concentration and bioavailability using Mehlich-3 solution were determined. For biological assessment, fresh weight and heavy metal uptakes were analyzed. It was revealed that AMDS reduced bioavailability most effectively, resulting in the decrease in heavy metal concentration in edible parts of all crops. When explaining the heavy metal uptake of plants, the bioavailability was more appropriate than the total contents of soil heavy metals. Therefore, bioavailability-based further research and management practices should be carried out continuously for the sustainable environment management, safe crop production, and human health risk reduction. 토양에서 중금속 안정화를 위하여 여러 종류의 개량제들이 연구되어왔다. 그러나 알칼리 토양에서 개량제들의 영향과 그에 따른 작물 가식부로의 중금속 전이에 대한 연구는 미비한 실정이다. 따라서 본 연구는 알칼리 토양에서 농작물의 가식부를 대상으로 중금속 안정화 효율 및 중금속 전이를 평가하기 위해 수행되었다. 중금속으로 오염된 광산 인근 농경지 토양에 3종류의 안정화제 (석회석, 제강슬레그, 산성광산배수슬러지)를 각각 3%씩 현장에 처리하였다. 6개월의 aging 이후 배추 (엽채류), 청경채(엽채류), 마늘 (근채류) 그리고 고추 (과채류)를 정식하고 표준영농교본에 준하여 재배하였다. 화학적 평가를 위해 토양 내 중금속의 총함량과 Melhich-3 용액을 이용한 생물유효도를 검정하였다. 생물학적 평가를 위하여 작물들의 생산량과 중금속 흡수량을 분석하였다. 그 결과, 산성광산배수슬러지 개량제의 유효도 저감 효과가 가장 우수하였으며 그에 따라 식물로의 중금속 전이 또한 감소하였다. 통계분석 결과 식물의 중금속 흡수를 설명하는 데에 있어 토양 내 중금속 총함량 보다는 생물유효도가 더 적합한 것으로 나타났다. 지속가능한 토양 환경의 관리, 안전한 농작물 생산, 그리고 중금속 흡수에 따른 인체 위해성 저감을 위하여 생물유효도에 기반한 연구가 지속적으로 수행되어야 할 것이다.